AKTUALISASI PERAN PEMERINTAH DALAM MENJAGA STABILITAS HARGA MELALUI MEKANISME TAS’ĪR: Studi Pendapat Wahbah al-Zuḥailī - noufal azmi (Journal of Sharia Economics, 2022)
The market mechanism in the Islamic muamalah system is based on the free market (free market, sūq al-ḥurrah). Moeslem Scholars agreed that the law of origin of pricing (tas'īr) was forbidden and should not be done. However, the fukaha are not cohesive in establishing the legal position of tas'īr when there is a tyranny or monopoly of iḥtikār goods. This study is a library research, with a conceptual approach. The study aims to find out the opinion of Wahbah al-Zuḥailī regarding the actualization of the role of the government in maintaining price stability through tas'īr, and also to know its relevance to the current context. The results showed that Wahbah Al-Zuḥailī recognized the ability of tas'īr when there was a need (al-ḥājah). The actualization of the role of the government in maintaining stability and normalization of prices can be carried out in the event of one of two indicators, namely the practice of iḥtikār and traders selling goods at a profit greater than 30% of the original price. The government is authorized and justified in imposing ta'zr administrative sanctions, such as imprisonment, fines, and shop closing sanctions (revocation of business licenses). Al-Zuḥailī's view is relevant to the current context, because in developing countries, especially in Indonesia, the government also has the authority to conduct market supervision, market intervention, and issue price policies when there is a shortage and prices of basic necessities are high. In Indonesia, the government's authority to maintain price stability is regulated in Law Number 7 of 2014. Keywords: Actualization, Government role, Price Stability, Tas'īr